The Impact of the COVID-19 Pandemic on Postpartum Readmission Rates at a Single Tertiary Care Center in New York City - DeBolt, Chelsea A.; Roig, Jacqueline; Spiera, Emily; Goldberger, Cody; Kaplowitz, Elianna; Toner, Lorraine; Stone, Joanne; Bianco, Angela (American Journal of Perinatology, 2022)
Objective The aim of this study was to mitigate transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and decrease exposure to the hospital setting, Mount Sinai Hospital implemented new protocols, including early postpartum discharge. Early discharge would allow for more single-bedded rooms, limiting exposure to other patients and their support persons. During the pandemic, patients were discharged to home on postpartum day 1 or 2 after vaginal or cesarean delivery, respectively, instead of day 2 or 3, unless longer hospitalization was needed for medical indications. We aim to determine if the readmission rate was increased in the setting of earlier discharge during the coronavirus disease 2019 (COVID-19) pandemic.Study Design Historical cohort study comparing the readmission rate in SARS-CoV-2 negative women who presented to Mount Sinai Hospital for delivery admission from March to May 2019 versus March to May 2020. The primary outcome was readmission rate within 6 weeks of discharge day. Maternal and neonatal characteristics and outcomes were compared between groups using t-tests or Wilcoxon's rank-sum test for continuous measures and chi-squared or Fisher's exact tests for categorical measures, as appropriate. Primary and secondary outcomes were assessed using linear and logistic univariable and multivariable regression.Results Patients in the 2020 cohort (n = 1,078) were significantly less likely to have public/state insurance (p = 0.02), more likely to have pregestational diabetes (p = 0.02), gestational diabetes (p = 0.04), gestational hypertension (p < 0.01), and an operative vaginal or cesarean delivery (vs. spontaneous vaginal delivery, p = 0.01) compared with 2019 cohort patients (n = 1,910). Patients in the 2020 cohort were significantly more likely to have an earlier postpartum day of discharge and a shorter median length of stay compared with 2019 cohort patients (both p < 0.01). Despite differences in length of stay, the rate of readmission was similar between the two groups (p = 0.45).Conclusion During the COVID-19 pandemic, there was no difference in readmission rate despite shorter hospital stays.Key Points
Keywords: coronavirus disease 2019; length of stay; pregnancy; readmission; SARS-CoV-2; postpartum